REINTERPRETING THE VALUE OF “RAHMATAN LIL ALAMIN” IN ISLAMIC RELIGIOUS EDUCATION AMID A GLOBAL GEOPOLITICAL CRISIS - Dewi Novianti; Zulfia Rizky; Saude Saude; Mohammad Djamil M Nur (Jurnal Konseling Pendidikan Islam, 2026)
The global geopolitical crisis, marked by armed conflict, ideological polarization, and increasing global intolerance, poses serious challenges for education in instilling humanitarian and peace values. In the Indonesian national context, the phenomena of radicalism, religious exclusivism, and the weak internalization of moderate religious values ​​indicate that Islamic Religious Education needs to be reactualized to present Islamic teachings as a blessing for all nature. Therefore, a study of the reactualization of the Rahmatan Lil Alamin value in Islamic Religious Education is crucial as an effort to strengthen an inclusive, humanistic, and civilized educational orientation. This study aims to analyze the concept, strategy, and relevance of the reactualization of the Rahmatan Lil Alamin value in Islamic Religious Education amidst the dynamics of the global geopolitical crisis. This study uses a qualitative approach with a literature review. Data sources come from the Quran, Hadith, scientific books, journal articles, and relevant academic documents. Data were collected through documentation techniques, analyzed using content analysis and thematic analysis, and validated through source triangulation and diligent literature review. The results of this study indicate that the reactualization of the Rahmatan Lil Alamin value in Islamic Religious Education can be achieved through strengthening the paradigm of religious moderation, integrating universal humanitarian values ​​into the curriculum, and developing dialogic and contextual learning practices. The implications of this research confirm its theoretical contribution to the development of an Islamic Religious Education paradigm oriented toward global peace, as well as its practical contribution to strengthening students' inclusive character in facing global geopolitical dynamics.